2020
DOI: 10.1242/dev.188821
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog specifies flight feather positional information in avian wings

Abstract: Classical tissue recombination experiments performed in the chick embryo provide evidence that signals operating during early limb development specify the position and identity of feathers. Here, we show that Sonic hedgehog (Shh) signalling in the embryonic chick wing bud specifies positional information required for the formation of adult flight feathers in a defined spatial and temporal sequence that reflects their different identities. We also reveal that Shh signalling is interpreted into specific patterns… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Molecular pathways involved in feather induction and morphogenesis have been extensively investigated in the past 20 years 4,8 . But little is known about how skin regional differences across‐the body are specified and how the formation of different types of feathers are controlled 9‐11 . This issue can be analyzed from the perspective of dermal control or epidermal differentiation 7,12 …”
Section: Introductionmentioning
confidence: 99%
“…Molecular pathways involved in feather induction and morphogenesis have been extensively investigated in the past 20 years 4,8 . But little is known about how skin regional differences across‐the body are specified and how the formation of different types of feathers are controlled 9‐11 . This issue can be analyzed from the perspective of dermal control or epidermal differentiation 7,12 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it should be taken into consideration that different types of regulatory innovations and their distinct co‐option mechanism can inform about the phylogenetic history of a structure (Tarchini & Duboule, 2006). For example, the Shh signalling pathway also contributes to positional information in the formation of adult flight feathers, involving the co‐option of a pre‐existing digit patterning mechanism (Busby et al, 2020). In the Emu's forelimb, a cardiac transcription factor ( NKX2.5 ) plays a role in outgrowth and wing patterning by inhibiting early limb bud expansion and subsequent muscle growth (Farlie et al, 2017; Newton & Smith, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Here we use GWAS to identify significant associations between genetic variation and the molt-migratory phenotype and find the strongest association with a SNP located within an intronic region on the GLI2 gene. GLI2 is a clear candidate for involvement in feather molt, as studies have shown it is a transcription regulator of the Sonic Hedgehog (Shh) signaling pathway that specifies positional information required for the formation of adult flight feathers 84 . Moreover, GLI2 activates and is co-expressed with Follistatin 85 , a gene that is linked to the development of hair follicles in mammals and feathers in birds as demonstrated by gene knockout experiments in Mus musculus 86 and ectopic induction of feather growth in Gallus gallus 87,88 .…”
Section: Discussionmentioning
confidence: 99%